1993
DOI: 10.1038/361162a0
|View full text |Cite
|
Sign up to set email alerts
|

Novel GABA responses from rod- driven retinal horizontal cells

Abstract: gamma-Aminobutyric acid (GABA) is the main inhibitory neurotransmitter in the central nervous system. Two classes of GABA receptors (GABAA and GABAB) have been identified. GABAA receptors are ligand-gated chloride channels that are competitively antagonized by bicuculline, noncompetitively blocked by picrotoxin, and often allosterically modulated by barbiturates and benzodiazepines. GABAB receptors regulate potassium and calcium channels through G-protein and intracellular second-messenger pathways, are select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
178
2
1

Year Published

1996
1996
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 252 publications
(194 citation statements)
references
References 23 publications
13
178
2
1
Order By: Relevance
“…The GABA A R initiates a large, fast-onset, rapidly desensitizing chloride current, whereas the GABA C R is relatively nondesensitizing, with slow activating and deactivating kinetics (Cutting et al, 1991;Qian and Dowling, 1993;Pan and Lipton, 1995). Amin and Weiss (1994) found that GABA subunits expressed in Xenopus oocytes produced a very slow activation (half-time of 9 sec at the GABA EC 50 ) and deactivation (half-time of 12.5 sec).…”
Section: Comparing Gaba and Glycine Receptorsmentioning
confidence: 99%
“…The GABA A R initiates a large, fast-onset, rapidly desensitizing chloride current, whereas the GABA C R is relatively nondesensitizing, with slow activating and deactivating kinetics (Cutting et al, 1991;Qian and Dowling, 1993;Pan and Lipton, 1995). Amin and Weiss (1994) found that GABA subunits expressed in Xenopus oocytes produced a very slow activation (half-time of 9 sec at the GABA EC 50 ) and deactivation (half-time of 12.5 sec).…”
Section: Comparing Gaba and Glycine Receptorsmentioning
confidence: 99%
“…The 1 receptor subunit was cloned from a retinal library (Cutting et al, 1991), and recombinant subunits exhibited GABA C properties (Zhang et al, 1995;Qian et al, 1997). Because responses in retina to GABA were highly similar to activation of these recombinant receptors, they were attributed to GABA C receptors (Feigenspan et al, 1993;Qian and Dowling, 1993;Zhang et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The electrical responses to GABA, which have been recorded from various types of retinal cells, are due to activation of both GABA A and GABA C receptors (10)(11)(12)(13)(14), and, except for a bicuculline-resistant GABA current seen in the golden perch retina (15), all other GABA C responses desensitize very slowly. For example, the GABA currents elicited in oocytes expressing GABA1 or its alternative spliced form (GABA1⌬51) decay only about 8% or less even after 10 min of exposure to GABA (4).…”
mentioning
confidence: 99%